Foglalkoztatási és jövedelemtermelési problémák vizsgálata a Balatoni turisztikai desztinációban (Problems with Employment and Income Generation in the Lake Balaton Tourism Destination) - Szilveszter Valentin (DETUROPE)
Since 2010 employment policies shifted greatly compared to the time between 1998 and 2002. After the elections the new government started to revise the policies concerning education and employment. The goal was to raise the number of employed people in Hungary to 4.7 million by the year 2020. In the national labour market there are areas that are unique and employ labour under special circumstances. Such an area is the Lake Balaton Resort Area, the 2nd largest tourist destination in Hungary. The Lake Balaton Resort Area consists of 179 settlements but most of its workforce comes from 43 settlements which have direct access to Lake Balaton. Most of the jobs are seasonal, lasting from May to September. Nowadays we hear from entrepreneurs that they are unable to find workers even though qualifications are not required anymore, because many skilled workers use the opportunities provided by the European Union, and go abroad to work, the primary target being Austria where they work in ski resorts during the winter, or London, where they can find full time jobs and earn wages 5 times that in Hungary. This is the case for the whole region of Balaton even outside the tourism sector. It is important to underline that the labour market in tourism influences the employment situation in all sectors of the region. In this paper I wish to examine how employment rates changed in the lakeshore settlements of the region in 2011, and how much income was generated by tourism employment around the lake. I examine the income generating capacity by the share of personal income tax that local government kept for themselves, and by the value of the income tax per employee, this latter indicator allowing the comparison of the Lake Balaton area to other tourism destinations in Hungary.